2021
DOI: 10.1089/phage.2020.0036
|View full text |Cite
|
Sign up to set email alerts
|

How Broad Is Enough: The Host Range of Bacteriophages and Its Impact on the Agri-Food Sector

Abstract: Novel bacteriophages (phages) possessing a broad host range are consistently and routinely reported, yet there is presently no consensus on the definition of ''broad host range.'' As phages are increasingly being used in the development of methods for the detection and biocontrol of human pathogens, it is important to address the limitations associated with the host range. For instance, unanticipated host range breadth may result in the detection of nonpathogenic targets, thereby increasing the false-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 105 publications
(134 reference statements)
0
11
0
Order By: Relevance
“…Collectively, phages are the main global predators of bacteria. However, individual phages tend to have narrow host ranges, often not even encompassing entire bacterial species; even when phages are found to infect taxonomically diverse bacteria, they typically do not infect broadly within those bacterial groups [ 1 , 2 , 3 , 4 , 5 ], and the diversity of bacterial anti-phage defense mechanisms virtually ensures an absence of systematically broad host ranges [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, phages are the main global predators of bacteria. However, individual phages tend to have narrow host ranges, often not even encompassing entire bacterial species; even when phages are found to infect taxonomically diverse bacteria, they typically do not infect broadly within those bacterial groups [ 1 , 2 , 3 , 4 , 5 ], and the diversity of bacterial anti-phage defense mechanisms virtually ensures an absence of systematically broad host ranges [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The six phages displayed different host ranges, indicating that they are distinct from one another. Host range is largely dependent on the ability of phages to bind to either a single receptor (i.e., narrow host range) or multiple different receptors (i.e., broad host range; Fong et al, 2021 ). Φ206, ΦMont, and Φ13314 showed very narrow host ranges, infecting only one or two tested Salmonella strains.…”
Section: Resultsmentioning
confidence: 99%
“…Host range is critical in the selection of phage candidates for biocontrol agents and detection applications. To be considered as excellent candidates for use as biocontrol agents in foods, phages should be strictly lytic and possibly have a broad host range ( Sharma et al, 2017 ; Fong et al, 2021 ; Picozzi et al, 2021 ). Since ΦEnt exhibited the broadest and unusual host range, formed clear plaques (possibly with high lytic activity), and had higher efficiency of plating (EOP) (data not shown), it was selected for further characterization of (with respect to) its growth kinetics, restriction pattern, and lytic profiles in model food systems and for determining its thermal stability.…”
Section: Resultsmentioning
confidence: 99%
“…(2019) , revealed that most of the SNPs found on Pseudomonas after exposure to DSM3 were also on membrane receptor. Additionally, different studies report that mutation in LPS genes induces phage resistance to Salmonella ( Rivera et al., 2019 ; Fong et al., 2020 ). This indicates that the most described mechanism for phage resistance in coevolution assays represent modification of protein receptors or exopolysaccharide, similar to the results found here.…”
Section: Resultsmentioning
confidence: 99%